Detecting aroma changes of local flavored green tea (Camellia sinensis) using electronic nose. (March 2018) - Ralisnawati, D; Sukartiko, A C; Suryandono, A; Triyana, K
Abstract: Indonesia is currently the sixth largest tea producer in the world. However, consumption of the product in the country was considered low. Besides tea, the country also has various local flavor ingredients that are potential to be developed. The addition of local flavored ingredients such as ginger, lemon grass, and lime leaves on green tea products is gaining acceptance from consumers and producers. The aroma of local flavored green tea was suspected to changes during storage, while its sensory testing has some limitations. Therefore, the study aimed to detect aroma changes of local flavors added in green tea using electronic nose (e-nose), an instrument developed to mimic the function of the human nose. The test was performed on a four-gram sample. The data was collected with 120 seconds of sensing time and 60 seconds of blowing time. Principal Component Analysis (PCA) was used to find out the aroma changes of local flavored green tea during storage. We observed that electronic nose could detect aroma changes of ginger flavored green tea from day 0 to day 6 with variance percentage 99.6%. Variance proportion of aroma changes of lemon grass flavored green tea from day 0 to day 6 was 99.3%. Variance proportion of aroma changes of lime leaves flavored green tea from day 0 to day 6 was 99.4%.